2018
DOI: 10.1002/da.22816
|View full text |Cite
|
Sign up to set email alerts
|

Exposure-based therapy changes amygdala and hippocampus resting-state functional connectivity in patients with posttraumatic stress disorder

Abstract: Enhanced amygdala and hippocampus rsFC with prefrontal cortical regions following PE could underlie improved capacity for inhibition and re-evaluation of threat, and heightened memory encoding and retrieval ability, respectively. These findings encourage further investigation of this circuitry as a therapeutic target in PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 56 publications
(86 reference statements)
4
64
2
Order By: Relevance
“…Our study also provides insight into how TF-CBT impacts neural connectivity based on heterogeneity of treatment response. TF-CBT has shown to increase amygdala and hippocampal connectivity to the orbitofrontal and medial prefrontal brain cortices 9 . This increase has been associated with improved capacity for inhibition and re-evaluation of threat and heightened memory ability 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study also provides insight into how TF-CBT impacts neural connectivity based on heterogeneity of treatment response. TF-CBT has shown to increase amygdala and hippocampal connectivity to the orbitofrontal and medial prefrontal brain cortices 9 . This increase has been associated with improved capacity for inhibition and re-evaluation of threat and heightened memory ability 9 .…”
Section: Discussionmentioning
confidence: 99%
“…TF-CBT has shown to increase amygdala and hippocampal connectivity to the orbitofrontal and medial prefrontal brain cortices 9 . This increase has been associated with improved capacity for inhibition and re-evaluation of threat and heightened memory ability 9 . Importantly, this increase in connectivity was to normal levels at the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Abdallah, Averill, Ramage, Averill, Alkin, et al (2019) found that in combat PTSD patients, PCT decreased connectivity within SN, whereas cognitive processing therapy increased connectivity within the Central Executive Network. In another study, X. Zhu et al (2018) reported increased rsFC in patients with PTSD between amygdala, hippocampus, and prefrontal regions following exposure therapy—a possible reflection of fear inhibition/extinction and memory processing.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of treatment studies focused on intrinsic brain activity, i.e., in rest and without a specific task (Napadow et al, 2012; Harris et al, 2013; Bosma et al, 2018). The effects of EXP specifically have also only been investigated using resting-state fMRI (Zhu et al, 2018), showing that patients with post-traumatic stress disorder showed enhanced post-treatment resting-state functional connectivity between the amygdala, orbitofrontal cortex, hippocampus and the medial PFC. To date, there have been no studies investigating how (EXP) treatment modulates the circuitry underlying pain-related fear in chronic pain.…”
Section: Introductionmentioning
confidence: 99%